Light‐weight thermal insulating fly ash cenosphere ceramics. Issue 6 (29th April 2018) - Urunkar, Yogesh; Pandit, Aniruddha; Bhargava, Parag; Joshi, Jyeshtharaj; Mathpati, Channamallikarjun; Vasanthakumaran, Sudarsan; Jain, Dheeraj; Hussain, Zakir; Patel, Shirish; More, Venumadhav
Abstract: Light weight fly ash cenosphere (FAC) ceramic composites were developed by simple slip casting method. Thermal properties, Bulk density, Microstructure, flexural strength, and phase analysis of the FAC ceramic composites were measured. The results proved that the FAC have ability to lower bulk density and thermal conductivity effectively. The lowest thermal conductivity achieved for FAC ceramic composites (0.27 W/m.K) was further reduced 0.21 W/m.K by adding combustible additives ie activated charcoal and corn starch. The flexural strength, bulk density and thermal conductivity of FAC ceramic composites reduced consistently with an increase in FAC content. The maximum flexural strength of 13.45 MPa was achieved with 50% FAC and the minimum flexural strength of 4.07 MPa was obtained with 80% FAC. The open porosity increased from 35.51% to 43.76% and 38.19% with an addition of 15% activated charcoal and corn starch, respectively, when compared to no additives. The bulk density of 699, 619, and 675 kg/m 3 was achieved with 80% FAC, 80% FAC with the addition of 15% activated charcoal and corn starch, respectively. The 80% FAC ceramic composite shows low thermal expansion coefficient 6.54 × 10 −6 /°C at the temperature of 50°C then it varies between 3.7 and 5 × 10 −6 /°C in the temperature range above 100°C. These results prove that the developed light weight FAC ceramic are excellent low‐cost thermal insulating materials.